Penggunaan Komputer dalam Pengajaran-Pembelajaran dalam kalangan Guru Sekolah Menengah: Satu Kajian Kes di Pulau Pinang (Computer Usage in Teaching and Learning among Secondary School Teachers: A Case Study in Penang) - Abdul Wahab Ismail Gani; Kamaliah Hj. Siarap; Hasrina Mustafa (Kajian Malaysia, 2006)
In the education field, computer usage in teaching and learning activities among teachers have become a priority. Continuous efforts made by the government to encourage computer usage among teachers are with the aim of producing a computer literate generation as well as sensitive to the current technological developments. In line with the government is efforts to encourage the usage of computers, it is timely to conduct a research on computer usage in teaching and learning in schools. This is to gauge the level of computer usage among teachers. A case study of a group of teachers from three schools in the North-East District of Penang, namely, SMK Abdullah Munshi, SMK Bukit Gambir and SMK Datuk Hj. Mohd. Nor Ahmad, was conducted. The objectives of the study were to measure the computer usage in teaching and learning as well as the factors that influence the computer usage. The Diffusion of Innovation theory has been applied and is fundamental for this research. Using the survey method, a questionnaire was developed and distributed to a total number of 184 teachers from the respective schools The results showed that there is no significant difference between male and female respondents, age categories and major subjects taught using computers in teaching and learning. However, factors such as knowledge, attitude, personality, support from organisations and innovation attributes of the computer (relative advantage, compatibility, complexity, trialibility and observability) were proven to have influenced computer usage in teaching and learning among teachers. Dalam bidang pendidikan, usaha mempertingkatkan penggunaan komputer dalam pengajaran dan pembelajaran terus dipergiatkan bagi melahirkan generasi muda yang celik komputer dan sentiasa peka dengan perkembangan teknologi semasa. Selaras dengan kesungguhan kerajaan menggalakkan penggunaan komputer dalam bidang pendidikan, adalah wajar satu kajian dilakukan untuk mengetahui tahap penggunaan komputer bagi pengajaran dan pembelajaran dalam kalangan guru-guru. Justeru itu, satu kajian kes dijalankan di tiga buah sekolah menengah Pulau Pinang. Teori Resapan Inovasi dijadikan asas untuk mengenalpasti tahap penggunaan komputer dalam pengajaran dan pembelajaran dan faktor-faktor yang mempengaruhinya. Kajian ini dijalankan dengan menggunakan kaedah tinjauan. Borang soal selidik telah diedarkan kepada 184 responden yang terdiri daripada guru-guru di ketiga-tiga sekolah tersebut. Keputusan kajian mendapati bahawa tiada perbezaan yang signifikan antara guru lelaki dan perempuan, antara kategori umur dan antara mata pelajaran major yang diajar dari segi penggunaan komputer dalam pengajaran dan pembelajaran. Faktor tahap pengetahuan, sikap, personaliti, sokongan organisasi dan sifatsifat inovasi komputer (faedah relatif, kesepadanan, kerumitan, kebolehcubaan dan keteramatan) didapati mempengaruhi penggunaan komputer dalam pengajaran dan pembelajaran dalam kalangan guru